2021
DOI: 10.1038/s41598-021-86037-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evolution of the epithelial cell secretome in preclinical 3D models of the human bronchial epithelium

Abstract: The human bronchial epithelium is the first line of defense against atmospheric particles, pollutants, and respiratory pathogens such as the novel SARS-CoV-2. The epithelial cells form a tight barrier and secrete proteins that are major components of the mucosal immune response. Functional in vitro models of the human lung are essential for screening the epithelial response and assessing the toxicity and barrier crossing of drugs, inhaled particles, and pollutants. However, there is a lack of models to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…FBS was supplemented because it was shown that Calu-3 cells require FBS to maintain a functional epithelium. In ALI cultures, a lack of FBS would also induce the hypersecretion of glycoproteins by Calu-3 cells [ 24 ]. Although Calu-3 cells can be infected without exogenous trypsin [ 2 ], we wanted to test whether the addition of trypsin would substantially boost IAV infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FBS was supplemented because it was shown that Calu-3 cells require FBS to maintain a functional epithelium. In ALI cultures, a lack of FBS would also induce the hypersecretion of glycoproteins by Calu-3 cells [ 24 ]. Although Calu-3 cells can be infected without exogenous trypsin [ 2 ], we wanted to test whether the addition of trypsin would substantially boost IAV infection.…”
Section: Resultsmentioning
confidence: 99%
“…In both 3D models, a functional epithelial barrier due to the presence of fibroblasts developed. Although Calu-3 cells are known to form tight junctions in 2D and 3D monocultures (e.g., [ 24 , 26 , 27 ]), we and others have shown that there is less ZO-1 protein present compared to cultures of normal bronchial epithelial cells [ 12 ] and to Calu-3/fibroblast 3D ALI co-cultures [ 28 ]. The use of standard inserts (e.g., with polyethylene terephthalate (PET) membrane) has also been shown to negatively influence the ZO-1 expression compared to 3D ALI models on collagen-hyaluronate scaffolds [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the safety of using 2% H 2 has was also proved through the work of Ohta et al [24][25][26]. Moreover, airway epithelial cells including A549 are alveolar cells, which prevent alveolar collapse by reducing surface tension, and NCI-H292 cells, which are located in the bronchi, act as a primary barrier for infection by secreting mucus and proteins [6,7]. Here, our study revealed the beneficial effect of 2% H 2 gas on alveolar (A549) and bronchial (NCI-H292) epithelial cells via its inhibition of MAPK signaling pathway proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, A549 cells reduce surface tension, which prevents alveolar collapse during respiration [6]. Similarly, NCI-H292 cells produce mucus and proteins in the bronchi, which forms a tight barrier for immune response [7]. Studies have shown that hydrogen peroxide (H 2 O 2 ) and lipopolysaccharide (LPS) can be used as a strong oxidizing agent to induce oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, different cell types, including mucus-producing goblet cells, ciliated cells, and non-ciliated cells, are arranged into a protective pseudostratified epithelium, depending on the airway segment [10,11]. Lung lining fluid, which consists of mucus in the upper airways and surfactant in the alveoli, protects the epithelia that line the respiratory tract through mechanical, antibacterial, and antioxidant activities [12,13]. As the airways are continually exposed to foreign agents and infections, airborne toxicants can potentially translocate through an intact or compromised epithelial barrier, generating possible systemic effects [12,14,15].…”
Section: Introductionmentioning
confidence: 99%